Pecuniary knowledge externalities across European countries: Are there leading sectors? - Agnieszka Gehringer (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2010)
This paper investigates empirically the occurrence of pecuniary knowledge externalities at the sectoral level across European economies. The main results suggest that, although some sectors can be considered as playing a particularly important role as a source of pecuniary knowledge externalities in the majority of examined countries, there exist significant national differences in the occurrence of these effects. Moreover, such external effects influence the dynamics of total factor productivity in downstream sectors and appear as a relevant source of growth in modern economies. As such, the concept of pecuniary knowledge externalities, as opposed to pure knowledge externalities postulated in the new growth theory, provides a new clue to understanding of the growth process.
Keywords: 330; pecuniary knowledge externalities; pure knowledge externalities; knowledge production function; intermediate goods transactions; Wissenstransfer; Lieferanten-Kunden-Beziehung; Branche; Innovation; Schlüsselsektor; Panel; Schätzung; Europa